Neurosteroids in Pain Management: A New Perspective on an Old Player - Joksimovic, Sonja L.; Covey, Douglas F.; Jevtovic-Todorovic, Vesna; Todorovic, Slobodan M. (Frontiers in Pharmacology, 2018)
Since the discovery of the nervous system’s ability to produce steroid hormones, numerous studies have demonstrated their importance in modulating neuronal excitability. These central effects are mostly mediated through different ligand-gated receptor systems such as GABAA and NMDA, as well as voltage-dependent Ca2+ or K+ channels. Because these targets are also implicated in transmission of sensory information, it is not surprising that numerous studies have shown the analgesic properties of neurosteroids in various pain models. Physiological (nociceptive) pain has protective value for an organism by promoting survival in life-threatening conditions. However, more prolonged pain that results from dysfunction of nerves (neuropathic pain), and persists even after tissue injury has resolved, is one of the main reasons that patients seek medical attention. This review will focus mostly on the analgesic perspective of neurosteroids and their synthetic 5α and 5β analogues in nociceptive and neuropathic pain conditions.